Body Mass Index and Pregnancy Outcome after Assisted Reproduction Treatment - Khaled Kasim; Ahmed Roshdy (Hindawi Limited, 2014)
The present study aimed to evaluate the impact of body mass index (BMI) on pregnancy outcome after intracytoplasmic sperm injection (ICSI). The study analyzed pregnancy outcome of 349 women who underwent ICSI by their BMI: <25, 25-<30, and ≥30 kg/m2. The associations were generated by applying logistic regression models. A significant reduction in positive pregnancy outcome was observed among overweight and obese women (odds ratio (OR) = 0.50; 95% confidence interval (CI) = 0.25-0.99 for overweight women and OR = 0.45; 95% CI = 0.20-0.89 for obese women). These estimates show that the pregnancy rates are reduced with increasing BMI. The effect of obesity on pregnancy outcome was absent when three and more embryos were transferred. Our study contributes to the reports linking overweight and obesity with decreased positive pregnancy outcome after ICSI and suggests women's age, infertility type, and number of embryos transferred to modify this reducing effect.